1991
DOI: 10.1002/arch.940170204
|View full text |Cite
|
Sign up to set email alerts
|

3‐oxoecdysteroid 3β‐reductase in various organs of the European corn borer, Ostrinia nubilalis (Hubner)

Abstract: Extracts of brains, subesophageal ganglia, Malpighian tubules, mandibular glands, proctodaea, salivary glands, testes, and fat body from mature fifthstage European corn borer larvae contain a 3-oxoecdysteroid 3P-reductase that converts 3-dehydroecdysone to an RIA-detectable ecdysteroid that has the same retention time (on HPLC and TLC) as ecdysone. Enzyme activity is destroyed by boiling, exposure to organic solvents, and treatment with trypsin. The reductase has a molecular weight in the range of 24-37 kD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The lack of 3-epimerization in O. nubilalis was an unexpected finding, as such a reaction is widespread in lepidopteran larvae (Weirich and Bell, 1997;Lafont et al, 2005). Our result is, however, consistent with the absence of 3-epimers detection in metabolic studies performed with various organs of O. nubilalis larvae (Gelman et al, 1991).…”
Section: Diversity Of Detoxification Pathways Against Ingested Ecdystsupporting
confidence: 87%
“…The lack of 3-epimerization in O. nubilalis was an unexpected finding, as such a reaction is widespread in lepidopteran larvae (Weirich and Bell, 1997;Lafont et al, 2005). Our result is, however, consistent with the absence of 3-epimers detection in metabolic studies performed with various organs of O. nubilalis larvae (Gelman et al, 1991).…”
Section: Diversity Of Detoxification Pathways Against Ingested Ecdystsupporting
confidence: 87%
“…3B,C). The molecular mass (36 kDa) of the enzyme was of the same order as those estimated by gel-exclusion chromatography in Manducn (20-30 kDa; [3,351) and Ostrinia nubilalis (25-27 kDa; [36]), and by SDS/PAGE in B. mori (42 kDa; Kinetic analysis of the haemolyph 3-dehydroecdysone 3 8 reductase revealed that the enzyme exhibits maximal activity at low 3-dehydroecdysone substrate concentrations, with a drastic ~321).…”
Section: Discussionsupporting
confidence: 54%
“…If 3-dehydroecdysone is envisaged as a prohormone, and the 3-dehydroecdysone 3P-reductase as an enzyme converting 3-dehydroecdysone to the more active ecdysone, not only in the haemolymph, but also in various other organs, such as the fat body, salivary glands, suboesophageal gland, Malpighian tubules, hindgut, brain [36] and midgut [21,40,411, the argument for a possible role for the enzyme in ecdysteroid activation is a persuasive one. For example, if 3-dehydroecdysone is sequestered into tissues, to be activated at specific points during development by the 3-dehydroecdysone 3P-reductase, this may account for the numerous observations that isolated abdomens moult in the absence of prothoracic glands (for review see [5]; [42]).…”
Section: Discussionmentioning
confidence: 99%
“…It seems unlikely, however, that such well developed structures as the larval SG would have evolved in the Culicidae if they had no physiological role to fulfill. In other insect species, larval salivary secretions have been associated with digestion (Verma and Baylan, 1972; Agarwal, 1976; Verma et al, 1977), immunity (Turillazzi et al,2004; Korayem et al,2004, Candido-Silva et al,2007; Liu, 2004), larval molting (Gelman et al, 1991; Zheng et al, 2003) and even social interaction (Cummings et al, 1999; Hunt, 1991). …”
Section: Introductionmentioning
confidence: 99%